Karakteristik Saluran (DL 7901TT) Terhadap Perubahan Beban - Zainal Abidin (ABEC Indonesia, 2022)
Parameters of resistance, inductance and capacitance on the lines of the electric power system will affect the reliability of the electric power system. The resistance (R) and inductance (L) parameters form a series impedance that is evenly distributed along the power line, while the capacitance (C) parameter occurs between the single-phase and neutral lines of the three-phase power line system. An increase in the value of the capacitor parameter (2uF, 4uF) on the line causes a voltage gain at the Overhead end of the line (U2 > U1), and an increase in the inductor parameter value (1,2H, 0.9H) on the line causes a weakening of the voltage at the Overhead end of the line (U2 < U1) with constant resistance parameter values (100%, 80%, 60%, 40%) . Current attenuation occurs when the end of the line is loaded with RC (U2 < U1) and current gain occurs when it is loaded with RL (I2 > I1). Changes in voltage and current affect PQ (PQ2 > PQ1). Significant gain occurs when the end of the channel is loaded with RC.